The weak link in the language teaching system and what to do about it - Moore, Eric (Kansas State University, 2009)
This thesis answers the questions: How should the terms interaction, individualization, and personalization be applied to Computer Aided Language Learning (CALL) software? What progress has been made in their implementation? How can CALL software developers better incorporate them in the future? For each of the three terms, I explain how it is applicable to the CALL software environment by defining it, describing the pedagogical research supporting it, and then giving general guidelines for incorporating it into a CALL software program. I measure the progress of the implementation of the three terms in CALL software through compiling and analyzing data from reviews of 44 software titles. The publication dates of the software titles are from 1981 to 2008. I propose through description and a proof-of-concept software program ways to improve the incorporation of the terms in question into CALL software. As a result of answering the three questions, this thesis shows that the current accepted definitions and ways of implementing interaction, individualization, and personalization need to be improved in order to comply with pedagogical research and make full use of current technology. The general guidelines given in the explanation of each term relative to CALL and the attributes under each term in the analysis of the compilation data provide examples of areas on which to focus development. Additionally, I specifically comment on pedagogically supported attributes within each term that have a weak representation in the software compilation and therefore need more development. In addition, this thesis is accompanied by “Mis vacaciones”, a proof-of-concept software program, which demonstrates ways to improve the incorporation of interaction, individualization, and personalization into CALL software. In “Mis vacaciones”, the learner takes a virtual trip to Nuevo Leon, Nicaragua. The multimedia sent to the learner by a previous traveler shows Nicaraguan city people and the La Gigatona festival. After visiting, the learner is asked to describe the Nicaraguans that they saw. If the learner needs help, Structured Input activities lead the learner to develop the third person singular imperfect form. Buttons in the software environment provide access to internet sources. The learner is able to draw and take photos to create a visual prop to aid in the description task.
Keywords: Structured Input; Computer aided language learning; Communicative Tasks; Interaction; Individualization; Software compilation; Education, Curriculum and Instruction (0727); Education, Technology (0710); Language, Modern (0291)